2021
DOI: 10.3892/or.2021.8170
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑8063 targets heterogeneous nuclear ribonucleoprotein AB to inhibit the self‑renewal of colorectal cancer stem cells via the Wnt/β‑catenin pathway

Abstract: The presence of cancer stem cells (CSCs) is a major cause of therapeutic failure in a variety of cancer types, including colorectal cancer (CRC). However, the underlying mechanisms that regulate the self-renewal of colorectal cancer stem cells (CRCSCs) remain unclear. Our previous study utilized CRCSCs and their parent cells; through gene microarray screening and bioinformatics analysis, we hypothesized that microRNA (miR)-8063 may bind to, and regulate the expression of, heterogeneous nuclear ribonucleoprotei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
1
5
1
Order By: Relevance
“…In addition, our study showed that CCAT1 knockdown activated the Wnt/β-catenin signaling pathway, which was inhibited by miR-8063 interference. These result are contrary to the previously reported roles of CCAT1 and miR-8063 in cancer [ 42 , 43 ]. We suspect that this is due to differences in the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, our study showed that CCAT1 knockdown activated the Wnt/β-catenin signaling pathway, which was inhibited by miR-8063 interference. These result are contrary to the previously reported roles of CCAT1 and miR-8063 in cancer [ 42 , 43 ]. We suspect that this is due to differences in the disease.…”
Section: Discussioncontrasting
confidence: 99%
“…The main role of EVs also includes their fusion with macrophages and other immune cells [ 30 , 31 ]. CSCs and their EVs are able to modulate cancer cell proliferation by the release of proteins [ 44 , 45 , 46 ] and miRNAs [ 30 , 47 , 48 , 49 , 50 , 51 ]. Examples are increasing, with results in favor or against cancer.…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%
“…The miR-92/PD-L1 pathway contributes to the suppression of immune cell function [ 30 ] and miR-200c stimulates the metastatic traits in colorectal cancer [ 47 ]. On the other hand, human liver cancer is attenuated in vitro and in vivo by miR-145 and miR-200 [ 48 ]; inhibition of lung metastasis is induced in osteosarcoma by miR-101 [ 49 ]; miR-8063 inhibits self renewal of GSC [ 50 ]; miR-663 inhibits the CSCs of a glioma [ 51 ]; and miR-1468-5p promotes a tumor immune escape [ 52 ]. Interestingly, many of the effects reported in this section, induced by CSCs and miRs, are mediated by the activation of various signaling pathways such AKT [ 22 , 46 ], GSK3-β [ 22 ], Wnt/β-catenin [ 22 , 23 , 50 , 51 ], and TGF-β/SMAD [ 53 ].…”
Section: Cscs and Their Evs Are Essential For Cancer Initiation And Its Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…By searching miRDB, 15 miRNAs were predicted to possess potential binding sites for PPP1R14B-AS1 (Table 1). Among these candidates, miR-134-3p [28], miR-8063 [29], miR-3135b [30], miR-765 [31], miR-4269 [32], miR-3168 [33] and miR-11181-3p [34] were reported to contribute to carcinogenesis and cancer progression; thus, they were chosen for further verification. Afterward, qRT-PCR was conducted to quantify these miRNAs in si-PPP1R14B-AS1-transfected breast cancer cells.…”
Section: Ppp1r14b-as1 Binds Directly To and Acts As A Sponge Of Mir-1...mentioning
confidence: 99%